"Etude d'une antenne imprimée à la fréquence 2.4Ghz " - مروة, زنقي; سعيدة, حسناوي; آسيه, برحومه (Université d'El Oued, 2021)
"New technologies have revolutionized the field of communications, leading to rapid development in the design of antennas by large frequency scale and access to miniature antennas with high capacities. The purpose of this note is to study the printed antennas, which are of great interest by researchers, which are antennas with an electromagnetic cavity, and substrates consisting of two insulating metal layers, It has a feeder hatch through which using feeding techniques, and have many advantages, lightweight, small size and cost, easy to manufacture. They are considered the best antennas in general. The design of the printed antennas is simulated using HFSS software, specifying reflection coefficient S11 and VSWR, to create antennas operating at a frequency of 2.4 GHz " "لقد أحدثت التكنولوجيات الجديدة ثورة كبيرة في مجال الاتصالات, أدى إلى التطوير السريع في تصميم الهوائيات على نطاق تردد واسع والوصول إلى هوائيات مصغرة ذات امكانيات عالية متعددة الاستخدامات في جميع القطاعات. ان الهدف من هذا العمل هو دراسة الهوائيات المطبوعة التي تشهد اهتماما كبير من قبل الباحثين, وهي هوائيات ذات سطح معدني وركائز تتكون من طبقة عازلة و أخرى أرضية و التي من خلالها تستخدم تقنيات تغذية, وتتميز بمزايا كثيرة, خفيفة الوزن , منخفضة الحجم والتكلفة, سهلة التصنيع. فهي تعد الامثل من بين الهوائيات بشكل عام. يتم محاكاة تصميم الهوائيات المطبوعة باستخدام برنامج HFSS , بتحديد معامل انعكاس S11 ، و نسبة موجات مستقرة VSWRلإنشاء هوائيات تعمل على تردد 2.4.GHz "
Systeme de telecommunication مذكرة ماستر تخصص
Keywords: Printed antennas, bandwidth, S11, power supply techniques, coupling, HFSS.; الهوائيات المطبوعة, نطاق التردد الواسع، S11, تقنيات التغذية, اقتران, HFSS.